Announcement of the Jubilee International Scientific Conference "Søren Kierkegaard in Our Time: Problems and Prospects of Modern Philosophy and Religious Studies" - Shevchenko, Serhii (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES)
We invite you to participate In the Jubilee International Scientific Conference «Søren Kierkegaard in Our Time: Problems and Prospects of Modern Philosophy and Religious Studies» (to the 200 th Anniversary of the Birth of Famous Danish Philosopher Søren Kierkegaard) The Conference will be held December 3-4, 2013 Kyiv – 2013